2004
DOI: 10.1016/j.trf.2004.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Predicting health outcomes and safety behaviour in taxi drivers

Abstract: These abstracts form the collection of papers which were presented in full at the 5th Australian Industrial/Organisational Psychology conference held in Melbourne, 26-29 July, 2003. Papers were accepted for either paper presentation or poster presentation following a peer-review process (2 reviewers per paper). The collection covers the full range of 1 / 0 topics. The 580 delegates who attended came from 18 different countries around the world, with the keynote speakers speaking on 'hot-topics' of interest to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 18 publications
1
20
0
2
Order By: Relevance
“…In another study, risky driving behavior among taxi drivers was linked to workplace hazards, aggression and drivers' perceptions of management's commitment to health and safety. 10 It can thus be deduced that the results of this study are comparable to those of most previous studies reported from developing countries.…”
Section: Knowledge and Attitude Of Taxi Driverssupporting
confidence: 88%
“…In another study, risky driving behavior among taxi drivers was linked to workplace hazards, aggression and drivers' perceptions of management's commitment to health and safety. 10 It can thus be deduced that the results of this study are comparable to those of most previous studies reported from developing countries.…”
Section: Knowledge and Attitude Of Taxi Driverssupporting
confidence: 88%
“…Higher scores on the scale indicated a higher level of perceived danger for certain actions while driving. The Cronbach alpha coefficient for a shorter (six item) version of this scale used by Machin and De Souza (2004) was .74.…”
Section: Risk Perception Scalesmentioning
confidence: 99%
“…Taxi drivers have been regarded as a unique group, one that has become popular for research (e.g., Botes, 1997;Burns & Wilde, 1995;Dalziel & Job, 1997;Machin & De Souza, 2004;Peltzer & Renner, 2003;Rosenbloom & Shahar, 2007). However, because most literature on taxi driving excludes findings on female drivers, let alone literature on females choosing taxi driving as a career, investigating such samples is difficult -especially speeding issues.…”
Section: Discussionmentioning
confidence: 99%